Mesocosm constructed wetland of canna indica for wastewater treatment - Tay, Xin Rou (2025)
Micropollutants like caffeine (CAF) in untreated wastewater pose significant ecological and health risks. Even at low concentrations, CAF disrupts aquatic organisms, inducing behavioral changes, oxidative stress, and developmental abnormalities. Zebrafish embryos, for instance, exhibit vascular disruptions and immune system activation, while goldfish show hyperactivity and aggression. Additionally, CAF affects marine invertebrates’ neurophysiology and impairs antioxidant activity, raising concerns about its cumulative ecological impact. Conventional treatment systems often fail to remove these contaminants, necessitating alternative solutions. This study evaluates mesocosm-constructed wetlands (CWs) with Canna indica, in monoculture and polyculture, for CAF and nutrient removal. Horizontal subsurface flow CWs with layered substrates (pebble, sand, gravel, cocopeat, activated carbon, and soil) were designed for optimal pollutant removal. Wastewater spiked with CAF (200 mg/L) was evenly distributed. Physico-chemical parameters (AN, BOD, and TN) and plant performance (biomass, chlorophyll, nitrogen uptake, lipid peroxidation) were analyzed to evaluate treatment efficiency and plant stress. Results showed the monoculture Canna indica system reduced CAF to 46.20 ± 0.09 mg/L, with significant decreases in AN (5.80 ± 1.98 mg/L), BOD (36.50 ± 2.12 mg/L), and TN (12.00 ± 1.41 mg/L). Polycultures performed slightly better, reducing CAF to 45.83 ± 0.51 mg/L, with higher TN and BOD removal. Lipid peroxidation analysis revealed the highest malondialdehyde (MDA) concentration in Heliconia psittacorum (0.0155 mM/g⁻¹), indicating elevated oxidative stress, while polyculture Canna indica showed the lowest MDA concentration (0.0070 mM/g⁻¹), reflecting reduced stress due to improved nutrient cycling and antioxidant defences. Polycultures also showed a 20.59% increase in BOD removal, a 0.19% improvement in removal efficiency, 5.88% higher nitrogen uptake, and a 47.37% decrease in MDA concentration compared to monocultures. This study demonstrates the potential of Canna indica for sustainable wastewater treatment, aligning with SDG 6 and SDG 14 to improve water quality and conserve ecosystems.